(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article analyzes the methods of using game technologies in technological education and their effectiveness in the educational process. The history and development of game technologies are studied, and the possibilities of developing practical skills, attracting attention and ensuring active participation of students through them in modern education are highlighted. Also, the article shows the role of game technologies in education, the formation of group cooperation and a creative approach based on foreign experience and local practices. Their importance in making the technological educational process more innovative and effective is analyzed.